Self-images in the present and future: Role of affect and the bipolar phenotype - Di,Simplicio M; Holmes,EA; Rathbone,CJ (JOURNAL OF AFFECTIVE DISORDERS, 2015)
BackgroundBipolar Spectrum Disorder (BPSD) is associated with changes in self-related processing and affect, yet the relationship between self-image and affect in the BPSD phenotype is unclear.Methods47 young adults were assessed for hypomanic experiences (BPSD phenotype) using the Mood Disorders Questionnaire. Current and future self-images (e.g. I am… I will be…) were generated and rated for emotional valence, stability, and (for future self-images only) certainty. The relationship between self-image ratings and measures of affect (depression, anxiety and mania) were analysed in relation to the BPSD phenotype.ResultsThe presence of the BPSD phenotype significantly moderated the relationship between (1) affect and stability ratings for negative self-images, and (2) affect and certainty ratings for positive future self-images. Higher positivity ratings for current self-images were associated with lower depression and anxiety scores.LimitationsThis was a non-clinical group of young adults sampled for hypomanic experiences, which limits the extension of the work to clinical levels of psychopathology. This study cannot address the causal relationships between affect, self-images, and BPSD. Future work should use clinical samples and experimental mood manipulation designs.ConclusionsBPSD phenotype can shape the relationship between affect and current and future self-images. This finding will guide future clinical research to elucidate BPSD vulnerability mechanisms and, consequently, the development of early interventions.